2015
DOI: 10.1039/c5cp03658e
|View full text |Cite
|
Sign up to set email alerts
|

Controllable photophysical properties and self-assembly of siloxane-poly(amidoamine) dendrimers

Abstract: Poly(amidoamine) dendrimers are typical luminescent polymers containing unconventional chromophores. A series of novel siloxane-poly(amidoamine) (Si-PAMAM) dendrimers were synthesized and investigated in this study. Their structures and properties were determined by NMR, XPS, LC/MS, and fluorescence spectroscopy. The introduction of Si-O-Si units in Si-PAMAM changed the photophysical properties of the dendrimers. The luminescence of Si-PAMAM was associated with the aggregation of its carbonyl groups, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…The photophysical properties and self‐assembly of siloxane–PAMAM dendrimers 175 ‐PG1 and 176 ‐PG2 were also studied. The outcomes confirmed that the fluorescence of Si–PAMAM could be changed by solvents, acids, metal ions, temperature, and aggregation degree of carbonyl groups ( Figure ) …”
Section: Aggregation Behavior Of Dendrimerssupporting
confidence: 59%
See 2 more Smart Citations
“…The photophysical properties and self‐assembly of siloxane–PAMAM dendrimers 175 ‐PG1 and 176 ‐PG2 were also studied. The outcomes confirmed that the fluorescence of Si–PAMAM could be changed by solvents, acids, metal ions, temperature, and aggregation degree of carbonyl groups ( Figure ) …”
Section: Aggregation Behavior Of Dendrimerssupporting
confidence: 59%
“…This is because acetone changed the aggregation of the carbonyl groups and physically influenced the configuration of Si–PAMAM. In water, Si–PAMAM aggregated because of its solubility, and the aggregation enhanced emission phenomenon was observed, which demonstrated that the fluorescence intensity was increased with the addition of volume fraction of water …”
Section: Aggregation Behavior Of Dendrimersmentioning
confidence: 98%
See 1 more Smart Citation
“…[6,19] Some reports attributed the emission to aggregation of carbonyl groups. [20] In the case of hyperbranchedp olyether epoxy,t he aggregation of the highly dense epoxy groups were responsible for fluorescencee mission. [12] However,t hesem echanismsw ere too specific to summarize the fluorescence emission for all of the nonconventional luminogens.…”
mentioning
confidence: 99%
“…Previous reportsh ave shown that the structural features of fluorescent polymers, dendrimers or supramolecular assemblies can easily make the nonconventional chromophores aggregated to form extended conjugation because of chain entanglement, dendritic effect, and intermolecularf orces. [11,20] Compared to these polymers, the presents iloxane derivatives are small and simple. In other words, the molecules should be theoretically monodispersed in dilute solutions, andt he conjugation should not be bulky enough to emits trong fluorescence.H owever, simple siloxane derivatives, including BSCN, BSMA and Si-PAMAM( Figure S5,S upporting Information), can emit bright blue fluorescence in dilute solutions.…”
mentioning
confidence: 99%